2021
DOI: 10.1109/access.2021.3052680
|View full text |Cite
|
Sign up to set email alerts
|

Neural Networks and Imbalanced Learning for Data-Driven Scientific Computing With Uncertainties

Abstract: Uncertainty quantification in complex engineering problems is challenging because of necessitating large numbers of expensive model evaluations. This paper proposes a two-stage framework for developing accurate machine learning-based surrogate models in structural engineering. The studied numerical model considers aleatory and epistemic uncertainties, i.e., ground motion features and material properties. Our framework's first step trains classification algorithms on the collected data from our numerical model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…ANN models are capable of capturing highly complex and non-linear relationships between inputs and outputs. 144,145 The models are inspired by the structure and functionality of the human brain. ANN models generally consist of three types of layers: an input layer, one or more hidden layers, and an output layer.…”
Section: Deep Learning Modelsmentioning
confidence: 99%
“…ANN models are capable of capturing highly complex and non-linear relationships between inputs and outputs. 144,145 The models are inspired by the structure and functionality of the human brain. ANN models generally consist of three types of layers: an input layer, one or more hidden layers, and an output layer.…”
Section: Deep Learning Modelsmentioning
confidence: 99%
“…Given that there are 112 elements in the feature vector as described in the next paragraph, we use overcomplete layers (i.e., larger than the input size) with all layers of the same size following the recommendations by Bengio. 58 The rationale for using two densely connected layers is based on previous studies 28,59 which found using one to three hidden layers to be effective. Note again that the objective herein is to have a surrogate architecture that is good enough to demonstrate the benefits of the 'data-centric' approach rather than focusing on optimization of hyperparameters (i.e., the 'model-centric' approach).…”
Section: Case Study Surrogate Model and Predictive Featuresmentioning
confidence: 99%
“…7-18, single-degree-of-freedom structures on liquefiable sand deposit, 19 reinforced concrete (RC) shear walls, 20 risk modeling of regional portfolios of structures, 14,15,18,[21][22][23][24] and estimation of collapse vulnerability of buildings. [25][26][27][28] However, similar to the general trends in the ML community, 29 the majority of the past research efforts focused on algorithmic developments or contrasting of the performance of different ML tools, while putting less emphasis on the most effective use of data. As an example of the latter, studies [30][31][32] focused on the use of stochastic surrogate models to better utilize results of linear and nonlinear response history analyses for risk assessments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To detect damages, predict seismic responses, and optimize sensor locations, the FEMs of some famous structures such as Guangzhou New TV Tower [37], Shanghai Tower [36,38], MIT Green Building [39,40], and Dalian World Trade Building [41] were simplified. Pourkamali-Anaraki and Hariri-Ardebili have presented a two-step uncertainty quantification method that uses a simplified alternative model of Milad Tower [42]. The classification of vibration-based damage detection methods is illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%